Pengetahuan Produk Investasi Syariah dan Literasi Keuangan terhadap Keputusan Investasi yang dimoderasi oleh Religiusitas: Studi pada Mahasiswa Perguruan Tinggi Islam dan Perguruan Tinggi Umum - Yudhi Kurniawan Zahari; Fachrozi; Kukuh Tondoyekti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The decision to invest in sharia among students of Islamic Religious Universities (PTAI) or public universities (PTU) can be influenced by several factors. A comprehensive understanding of Sharia-compliant investments' concepts, types, and characteristics can significantly influence an individual's propensity to invest according to Islamic principles. This study aims to investigate the impact of Sharia investment product knowledge and financial literacy on PTAI and PTU students' investment decisions, with religiosity as a moderator. This study will use a quantitative approach using the survey method. The data collection process will involve administering questionnaires to a purposively selected sample of students through an online survey or direct distribution on campus. The hypotheses were tested using the Smart PLS version 4.1 program. The results showed that Product Knowledge and Financial Literacy variables affect the Investment Decisions of PTAI students. While Religiosity only moderates the effect of Product Knowledge on the Investment Decisions of PTAI Students, Product Knowledge and Financial Literacy do not affect the Investment Decisions of PTU Students. Religiosity cannot moderate Product Knowledge and Financial Literacy on Investment Decisions of PTU Students.